Analisis Multifaktor Terhadap Pemanfaatan Layanan Gawat Darurat di Rumah Sakit Islam Sakinah Mojokerto - Martiana; Ernawati Ernawati; Ahmad Lathifi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of facilities, brand awareness, and brand image on the utilization of emergency department services at Sakinah Islamic Hospital Mojokerto, which has experienced a decline in visits since 2018. The research design uses a quantitative observational approach with a cross-sectional method on 122 respondents selected through systematic random sampling from communities within a 3 km radius of the hospital. Data were collected using questionnaires and analyzed using multiple linear regression. The results showed that facilities (p=0.000), brand awareness (p=0.000), and brand image (p=0.002) significantly influenced emergency department utilization with a contribution of 83.4%. Facilities variable was the most dominant factor with a regression coefficient of 0.478, followed by brand awareness (0.431) and brand image (0.158). Efforts to increase emergency department utilization require a comprehensive strategy focusing on improving facility quality, strengthening brand awareness, and building a positive brand image in accordance with the needs and expectations of the community. Keywords: facilities, brand awareness, brand image, emergency department utilization, hospital